Supply chain of sugarcane and its lignocellulosic biomass biorefineries in Argentina: an optimal design approach - Machin Ferrero, Lucas M. (2021)
The sugarcane, a vast agricultural resource, is a key source for sustainable processes yielding biofuels and bioproducts. Tucumán province in Argentina is the main national sugarcane producer with the potential to fully take profit of this biomass in biorefineries. This study focuses on the use of mathematical programming to make strategic decisions in the Argentinean sugarcane industry. The main goal is to transform the traditional production scheme in a complex of biorefineries, which produce multiple products while making an integral use of biomass. The design task is formulated as a mixed-integer linear model (MILP) that seeks to minimize the total cost of the network. The capabilities of the proposed optimization framework are illustrated through a case study based on three real-scaled scenarios. The solutions provide valuable insight into the design problem and suggest different SC topologies.